1994
DOI: 10.1007/bf00967705
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic haloperidol treatment on dopamine-induced inositol phosphate formation in rat brain slices

Abstract: The effects of chronic haloperidol administration on the accumulation of inositol phosphates were examined in rat brain slices pre-labeled with [3H]myo-inositol and incubated with various dopaminergic drugs. Rats were treated with haloperidol-decanoate or its vehicle (sesame oil) for two, four or six weeks. Dopamine and the selective D1 agonist, SKF38393, induced a significant increase in lithium-dependent accumulation of [3H]inositol monophosphate (IP1) in the frontal cortex, hippocampus and striatum of vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Prior drug use is clearly a major concern, and a number of psychoactive compounds, including antipsychotic drugs, were detected in some of these schizophrenic brain samples. In several previous studies in animals, treatments with antipsychotic drugs have been reported to decrease phosphoinositide signaling (Friedel and Knauer, 1981;Edwards et al, 1991;Li et al, 1992Li et al, , 1994. If this action of antipsychotic drugs also occurs in humans, these drugs would be predicted to dampen the increased phosphoinositide signaling detected in schizophrenic brain in this study.…”
Section: Phosphoinositide Signaling In Schizophreniamentioning
confidence: 63%
“…Prior drug use is clearly a major concern, and a number of psychoactive compounds, including antipsychotic drugs, were detected in some of these schizophrenic brain samples. In several previous studies in animals, treatments with antipsychotic drugs have been reported to decrease phosphoinositide signaling (Friedel and Knauer, 1981;Edwards et al, 1991;Li et al, 1992Li et al, , 1994. If this action of antipsychotic drugs also occurs in humans, these drugs would be predicted to dampen the increased phosphoinositide signaling detected in schizophrenic brain in this study.…”
Section: Phosphoinositide Signaling In Schizophreniamentioning
confidence: 63%
“…These observations have been made in preparations of the rat kidney (Felder et al, 1989a; Felder et al, 1989b; Vyas et al, 1992a; Hussain and Lokhandwala, 1997), rat brain (Alexander and Crutcher, 1990; Undie and Friedman, 1990a; Undie and Friedman, 1990b; Arias-Montano et al, 1993; Martin and Waszczak, 1993; Li et al, 1994), mouse brain (Friedman et al, 1997; Undie, 1998), postmortem human brain (Wallace and Claro, 1993; Pacheco and Jope, 1997), fresh monkey brain (Panchalingam and Undie, 2001) and clonal cell lines of rat hippocampal origin (Jin et al, 1998). The findings are in contrast with some earlier reports that had implied a lack of association of dopamine with phosphoinositide hydrolysis in neural tissues or clonal cell lines (Pizzi et al, 1987; Cubitt et al, 1987; Pizzi et al, 1988; Rubinstein and Hitzemann, 1990).…”
Section: Signaling Cascades Associated With D1-like Receptor Stimumentioning
confidence: 93%
“…Multiple laboratories have demonstrated that dopamine as well as D 1 -like receptor agonists can activate PLC-mediated phosphoinositide hydrolysis in native mammalian tissues (Felder et al, 1989a; Felder et al, 1989b; Dyck, 1990; Chen et al, 1992; Vyas et al, 1992a; Martin and Waszczak, 1993; Li et al, 1994; Kansra et al, 1995; Pacheco and Jope, 1997; Hussain and Lokhandwala, 1997; Friedman et al, 1997; Rosengarten and Friedhoff, 1998; Jin et al, 1998; Jope et al, 1998). These observations have been made in preparations of the rat kidney (Felder et al, 1989a; Felder et al, 1989b; Vyas et al, 1992a; Hussain and Lokhandwala, 1997), rat brain (Alexander and Crutcher, 1990; Undie and Friedman, 1990a; Undie and Friedman, 1990b; Arias-Montano et al, 1993; Martin and Waszczak, 1993; Li et al, 1994), mouse brain (Friedman et al, 1997; Undie, 1998), postmortem human brain (Wallace and Claro, 1993; Pacheco and Jope, 1997), fresh monkey brain (Panchalingam and Undie, 2001) and clonal cell lines of rat hippocampal origin (Jin et al, 1998).…”
Section: Signaling Cascades Associated With D1-like Receptor Stimumentioning
confidence: 99%